(untitled) (Journal of actual problems of jurisprudence, 2019)
International Covenant on Civil and Political Rights guarantees the right to be protected by legal counsel of his choice. This right is one of the fundamental pillars of a fair trial, as it provides the main condition for full protection – trust between the accused and his lawyer, and also eliminates the abuse of the trust and the professional status of the defense at all. The basis of the legal status of the attorney constitute not only the powers enumerated in the law , but a set of legal mechanisms to implement these powers . Among these mechanisms , inter alia, include the guarantee of the independence of the lawyer’s law enforcement agencies of the state in the exercise of their professional obyazannostey. Statya 17 of the Law of the Republic of Kazakhstan “On Advocacy “ contains a very extensive list of guarantees of this activity , including but not limited to a ban on obstructing its implementation , privacy advocates records and related materials , the ban on denial of visits and much more. Keywords: human rights and freedoms, lawyer, advocacy, suspect, accused.